The complete book of Christian heroes over 200 stories of courageous people who suffered for Jesus - Jackson, Dave; Jackson, Neta (Wheaton, IL Tyndale, 2005)
Includes bibiographical references and indexes.
Includes biographical studies of Jim Elliot, Stanley Dale, Graham Staines and his sons, Watchman Nee, etc.
Keywords: Christian martyrs -- biography